Stakeholders’ perceptions of the innovation trends in the Slovak forestry and forest-based sectors - Loučanová, Erika; Paluš, Hubert; Báliková, Klára; Dzian, Michal; Slašťanová, Nikola; Šálka, Jaroslav (Journal of Business Economics and Management, 2020)
Innovations represent the engine of the business and economic. This is particularly relevant to the traditional sectors such as forestry and forest-based industry that are expected to play an important role in the future steps oriented towards meeting the sustainable development goals. The main aim of this study is to analyse the stakeholders’ perceptions of the innovation trends in the forestry and forest-based sectors by using a Q-methodology. This research addressed three groups of respondents in Slovakia, whose task was to subjectively assess innovative trends in the forestry and forest-based sectors. Based on the results it can be concluded that the innovation trend in the forestry and forest-based sectors will be oriented towards the technological progress focused on the increasing efficiency of wood processing and increasing the usability of waste material as well as the trend of increasing development of innovations in the forest recreation services.